Role of social capital and social value creation in augmenting sustainable performance of social enterprises: Moderating role of social innovation - Samar Hayat Khan; Muhammad Yasir; Hassan Ahmed Shah; Abdul Majid (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2021)
The last two decades represented the scarce discussion of the organizational social capital (SC) and its impact upon the social enterprises' sustainable performance in the developing economies like Pakistan. The main objective of this research is to analyze the impact of social capital on sustainable performance (SP) of social enterprises working in the context of developing economies. This research also tested the mediating role of the social value creation in the relationship of social capital and sustainable performance of social enterprises. Moreover, the contingent effects of social innovation (SI) were also evaluated upon the association of social capital and social enterprises' sustainable performance. Study utilized the deductive reasoning by applying the quantitative method. Data was gathered from the 171 managerial level employees of the 57 social enterprises working in Pakistan. Correlation analysis, regression analysis and Normal test theory was used as statistical test utilizing SPSS v.23. The statistical results confirmed that all the predictor constructs significantly elucidate the consequence constructs. Mediation analysis results also confirm that social value creation mediates the association of social capital and sustainable performance. Similarly, moderation analysis also confirms the moderating role of the social innovation upon the association of social capital and social enterprises' sustainable performance. This study enriches the available theory through evaluating the mediating role of social value creation and moderating role of social innovation on social capital-sustainable performance link, thus makes a significant contribution to prevailing theory contextualizing the social enterprises of developing economies by emphasizing upon the associations among social capital, social value creation, social innovation and sustainable performance.
Keywords: 330; social capital; social value creation; social innovation; sustainableperformance; social enterprises; enterprise' age; enterprise' size; Pakistan